2000
DOI: 10.1080/00984100050194117
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Pathological Effects of Cadmium Ingestion on Pekin Ducks Exposed to Saline

Abstract: This study examined the effects of simultaneous exposure to saline and cadmium (Cd) on organ mass and histology of a bird with salt glands, the Pekin duck, Anas platyrhynchos. Three mixed-sex groups, each containing 6 birds, ate duck pellets containing 0, 50, or 300 microg Cd/g, respectively, for 4 1/2 mo and drank 300 mM NaCl. Only females on the high-Cd diet lost body mass. Ingestion of Cd reduced heart mass in females. There was increased mass of Harderian and salt glands in both sexes. Mass of kidneys and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Statistical analysis revealed that differences between the group of embryos exposed to 1 µg of cadmium and the control and sham groups was significant at 0.05, while differences between the control and sham groups and the group injected with 5 µg of cadmium were significant at 0.01 (Table 2). Similar changes in heart weight in female Pekin ducks exposed to cadmium were observed by Hughes et al (2000). A decrease in relative heart weight in broiler chickens receiving dietary cadmium was also described by Bokori et al (1996).…”
Section: Resultssupporting
confidence: 81%
“…Statistical analysis revealed that differences between the group of embryos exposed to 1 µg of cadmium and the control and sham groups was significant at 0.05, while differences between the control and sham groups and the group injected with 5 µg of cadmium were significant at 0.01 (Table 2). Similar changes in heart weight in female Pekin ducks exposed to cadmium were observed by Hughes et al (2000). A decrease in relative heart weight in broiler chickens receiving dietary cadmium was also described by Bokori et al (1996).…”
Section: Resultssupporting
confidence: 81%
“…The toxicity of this metal was previously demonstrated in vertebrates and birds in particular (Hughes et al 2000).…”
Section: Trace Element Distribution and Toxicity Significancementioning
confidence: 93%
“…Previous studies have shown an impact of cadmium on organs such as kidneys (Hughes et al 2000). These impairments have often been observed on very high contamination levels which are not relevant with concentrations found in natural environments or with Cd levels recorded in wild bird species.…”
Section: Bioaccumulationmentioning
confidence: 94%
“…For instance, in Alaska, very high levels of cadmium were reported in kidneys of Spectacled eiders (Somateria fischeri) (Trust et al 2000). These levels can lead to various effects on organisms such as the induction of inflammation of renal interstitium and marked degenerative changes in testes (Hughes et al 2000). However, few studies have focused on the possible impact of this non essential element on cellular metabolism of aquatic birds.…”
Section: Introductionmentioning
confidence: 98%